Recency and rarity effects in disambiguating the focus of utterance: A developmental study. - Reiki Kishimoto; Kazuhide Hashiya (PLoS ONE)
While the communicator's intended referent in a conversation may not be immediately apparent, effective communication often overcomes this ambiguity. However, the specific mechanisms through which children use various cues to pinpoint the referent remain unclear. The communicator determines what is salient from the receiver's perspective. In return, the receiver identifies what the communicator identifies to be relevant for the receiver. The current study focused on two salient cues: rarity and recency, because rarity results in surprise and recency means a cue is more easily perceived and remembered. The current study investigated how adults and children aged 7-10 employ rarity and recency cues embedded in a series of events to clarify the referent intended by the communicator. Participants observed sequences comprising one rare and eight frequent events. An utterance, "Did you see that?" was presented at the end of each sequence, and participants identified the event(s) referred to by "that." Events that were rare and close to the utterance were more likely to be identified as the referents. Notably, the utilization of these cues differed between adults and children. For adults, the recency effect manifested gradually, with events closer to the utterance identified more frequently, and it exhibited an interaction with rarity. Among children, the recency effect was absolute, as the event closest to the utterance held a higher likelihood of being identified, and this effect was not influenced by rarity. Two additional conditions eliminated potential response biases and memory-related confounds. Our research suggests that school-age children are capable of disambiguating utterances by factoring in that the events they find salient are likely to be the communicator's focus. However, they are still in the process of developing reasoning skills similar to those of adults.